Self-Medication Patterns with Non-Steroidal Anti-inflammatory Drugs Among Healthcare Workers in Alkoms City: Analysis of Causes, Effects, and Preventive Strategies - Ibrahim Dukali; Ahlaam Amteer; Naema Salem; Ahed Al-Shubeir; Afaf Al-Sharif; Wafa Al-Taeb (AlQalam Journal of Medical and Applied Sciences, 2026)
Self-medication with non-steroidal anti-inflammatory drugs (NSAIDs) without medical supervision represents a significant global public health concern, as it may lead to preventable adverse drug reactions and increased healthcare costs. This study looks at how common it is for healthcare workers and residents in Alkoms City, Libya, to take NSAIDs without a prescription. It also looks at the social and behavioral factors that lead to this, how they affect people, and how they can be stopped using evidence-based methods. A structured, validated questionnaire was used to conduct a descriptive, community-based, cross-sectional study with 100 randomly chosen adult subjects (most of whom were healthcare workers). The questionnaire asked about the subjects’ racial and ethnic background, how often they used drugs, how much they knew about their uses and risks, and how they felt about seeing a doctor. We used SPSS version 26 to look at the data and descriptive statistics, and Chi-square tests to find links. A significant proportion of participants (20%) reported purchasing NSAIDs without prior medical consultation, indicating the presence of self-medication practices within the study population, which is also known as self-medication. A notable difference between male and female participants was observed, with males demonstrating a higher tendency toward self-medication practices: men (65%) were more likely to self-medicate than women (35%), which may be because of cultural norms about how people should act when they are looking for health care. Notably, 90% of those who answered said they had never had formal training in how to keep medications safe. This is a worrying result considering that 75% of the sample were healthcare workers. A statistically significant positive link was found between having more education and using medications correctly (p<0.05), which supports the idea that education is a major social factor that affects health. These results show that organized public health programs to help people learn more about medications are needed right away, and that rules about drugs need to be strictly enforced. NSAID self-medication and the health problems that come with it are becoming a bigger problem that needs more than one solution.